Renessans Helps in Early Clearance of SARS-CoV-2: In-Vivo Activity of the Iodine Complex in Rhesus macaque - Muhammad Nawaz; Muhammad Adnan Ashraf; Muhammad Asad Ali; Muhammad Zubair Shabbir; Muhammad Abu Bakr Shabbir; Imran Altaf; Sohail Raza; Saira Rafique; Sohail Hassan; Nageen Sardar; Adnan Mehmood; Muhammad Waqar Aziz; et al. (Life, 2022)
Iodine complexes have known antimicrobial properties along with reported in-vitro antiviral activity for several viruses. Renessans is one such product with iodine complexes and ascorbic acid. The present study was designed to determine its efficacy for SARS-CoV-2 in Rhesus macaque. Rhesus macaque were assigned to: A) prophylactic group (n = 3), (B) treatment group (n = 3), (C) infection control group (n = 4), and (D) negative control group (n = 4). Groups A, B, and C were challenged with 2 × 106 TCID of SARS-CoV-2. The prophylactic group (A) was administered Renessans from 5 days before infection till 8 days postinfection (DPI). The treatment group (B) was administered Renessans from 3 till 8 DPI. Group C was administered water-insoluble fractions only. Nasal swabs from all monkeys of groups A, B, and C remained positive for SARS-CoV-2 till 2 and 7 DPI, while the swabs became negative for groups A and B at 14 DPI. Likewise, fecal matter of monkeys in group A returned negative results during the experiment, while that of group B had significantly decreased viral load (101.5 genome copies/mL) compared to group C (103 genome copies/mL). Hence, it is concluded that Renessans has in-vivo SARS-CoV-2 activity and may result in early clearance of SARS-CoV-2.